Hurricanes, economic growth and transmission channels: Empirical evidence for countries on differing levels of development. (May 2018) - Berlemann, Michael; Wenzel, Daniela
Highlights: We study medium- and long-run consequences of hurricanes in a large panel dataset. We find negative long-run effects of tropical storms in our full country sample. The effects strongly depend on the level of development of the afflicted countries. Especially the low-income countries experience strongly negative growth effects. We also deliver an analysis of possible channels through which hurricanes affect economic growth. Abstract: While the short-term growth consequences of natural disasters are comparatively well studied, little is known about the long-run perspective. Based on truly exogenous storm indicators, derived from a meteorological database, we show that the growth effects of tropical storms go well beyond the short-term perspective. A disaggregated analysis reveals that the reaction of economic growth to the occurrence of hurricanes depends strongly on the level of development of the afflicted countries with developing countries being most negatively affected. We also consider through which channels tropical storms affect long-run growth and find the investment share as well as fertility to react systematically to tropical storms.